PENGARUH UNIT KEGIATAN MAHASISWA (UKM) PRAMUKA TERHADAP PEMBENTUKAN KARAKTER JUJUR MAHASISWA UNIVERSITAS RIAU: (Effect of Unit Program Activity University (SME) Pramuka on the Establishment of High Character Students of Riau University) - Jumili Arianto (Perspektif Pendidikan dan Keguruan, 2017)
The purpose of National education is to develop the ability and to form the characterand dignified civilization in order to educate the life of nation, to develop the students’potential in order to be a religious man and cautious to the God almighty, noble,healthy, competent, creative, independent, and democratic citizen and responsible. TheIndonesian government plan the nation culture and character development begun by thedeclaration of education of culture and character of nation as a national movement inthe beginning of january 2010. This plan is reconfirmed in the president’s speech on theNational Education Day May 2, 2010. The purpose of this research is to know whetherthe scout student activity units takes effect to the scout students honest characterdevelopment of Riau University. The methodology in this research is DescriptiveQualitative. The population of this research is all the active scout members front groupRiau University 2016 which amount to 80 people. The result of recapitulation foundthat the respondents are dominant to choose the statemen” unberdened on doingsomething “ which are 64 respondents or 80%, while the less dominant is the statement“ being honest and polite to parents “ which are 5 respondents or 6.25%. If the databecomes a benchmark is very often (SS) and often (S) so the total is 80,41%.Therefore, it can be concluded that the level of honesty of scout student activity units isin the very good level.